Development of the Brief Personal Values Inventory for Sense of Values. (18th February 2020) - Ozawa, Sachiyo; Iijima, Yudai; Ando, Shuntaro; Okada, Naohiro; Kawashima, Tomoko; Ohta, Kazusa; Yamasaki, Syudo; Kasai, Kiyoto; Nishida, Atsushi; Nakatani, Hironori; Koike, Shinsuke
Abstract: The Portrait Values Questionnaire (PVQ) is a widely used questionnaire for assessing sense of values; however, it is difficult to apply for children and adolescents. Therefore, the present study aimed to develop a questionnaire for sense of values, called the Brief Personal Values Inventory (BPVI), consisting of simple questions and fewer items compared to the PVQ. We first created 12 items for the BPVI and then tested criterion‐related validity with values in the PVQ‐57 in 167 Japanese general population participants (81 males, mean age [ SD ], range: 23.4 [8.2], 15–57 years). Each of these items was correlated with one or more of the values in the PVQ‐57 and covered all higher‐order values in Schwartz's theory (openness to change, self‐enhancement, conservation, and self‐transcendence). In summary, the BPVI adequately corresponded with Schwartz's value theory, indicating an acceptable criterion‐related validity. This questionnaire is applicable to a wide population, including adolescents, and will be a useful tool for researchers to elucidate the developmental pathway of personal sense of values.